Clinical Holistic Medicine: Holistic Rehabilitation - Søren Ventegodt; Mark Gringols; Joav Merrick (The Scientific World Journal)
Quality of life, health, and ability are often lost at the same time and most often in one decaying existential movement over 5 or 10 years. This “lost life” is mostly too slow to be felt as life threatening, but once awakened to reality, it provokes the deepest of fears in patients: the fear of death itself and destruction of our mere existence. The horrible experience of having “lost life”, often without even noticing how it happened, can be turned into a strong motivation for improvement. Personal development is about finding the life deeply hidden within in order to induce revitalization and rehabilitation. Rehabilitation is about philosophy of life with the integration of the repressed painful feelings and emotions from the past and the letting go of the associated negative beliefs and decisions. The holistic medical toolbox builds on existential theories (the quality of life theories, the life mission theory, the theory of character, the theory of talent, and the holistic process theory) and seems to have the power to rehabilitate the purpose of life, the character of the person, and fundamental existential dimensions of man: (1) love; (2) strength of mind, feelings, and body; and 3) joy, gender, and sexuality; allowing the person once again to express and realize his talents and full potential. The principles of rehabilitation are not very different from other healing, but the task is often more demanding for the holistic physician as the motivation and resources often are very low and the treatment can take many years.